A systematic review of whether the number of linguistic errors in medical interpretation is associated with the use of professional vs ad hoc interpreters - Iben Gad Lauridsen; Morten Deleuran Terkildsen; Lisbeth Uhrskov Sørensen (Archives of Public Health)
Abstract Medical consultations depend on a shared linguistic understanding between the patient and physician. When language concordance is not possible, interpretation is required. Prior studies have revealed that professional in-person interpretation (PIPI) results in patients reporting higher satisfaction and a better understanding of things the physician explained. Despite this, language-discordance often results in using family and/or friends for ad hoc interpretation. This systematic review examines the linguistic aspect of medical interpretation by assessing the number of linguistic errors made and their relation to professional in-person interpretation (PIPI) or in-person ad hoc interpretation (IPAHI). PIPI was defined as people employed as interpreters, but with no specific requirements for education or experience. This systematic review examines studies comparing the number of errors when using PIPI and IPAHI. We performed a PICO-criteria-based search in five scientific databases. We screened English and Danish studies published between 1995 and October 2024. Furthermore, we screened references from, and citations of the included articles. We used the appropriate Cochrane Tool for risk of bias assessment. We identified six studies using a PICO search and one additional study by snowballing. The included studies revealed critical methodological differences, and consequently a statistical synthesis of results was not conducted. We found indications that the number of interpreting errors was significantly lower when using PIPI than family members for IPAHI. Interpreting error rates were not significantly lower when comparing PIPI to the use of medical staff without interpretation training for IPAHI. Generally, we found that the difference between PIPI and IPAHI tended to be more prominent when dealing with more severe diagnoses, e.g., incurable cancer. The methodological differences between included studies and the risk of bias within included studies limit the conclusions drawn in this review. Also, no other kinds of interpretation than PIPI and IPAHI were considered, and the recommendations are solely based on accuracy. Considering these limitations and the fact that no other systematic reviews within this highly specific topic exist, this review resulted in the following recommendations: 1) Professional in-person interpretation should be the first choice in language-discordant medical consultations. 2) If professional interpretation is not possible, using medical staff without interpretation training should be chosen before interpretation by family or friends. 3) All consultation participants should keep sentences short and straightforward, as this is related to a lower risk of omissions in interpretation.